Characterization of Aspergillus fumigatus CAS-21 tannase with potential for propyl gallate synthesis and treatment of tannery effluent from leather industry - Cavalcanti, Rayza Morganna Farias [UNESP]; Jorge, João Atílio; Guimarães, Luis Henrique Souza [UNESP] (My University, 2018)
One of the tannase isoforms produced by the fungus Aspergillus fumigatus CAS-21 under submerged fermentation (SbmF) was purified 4.9-fold with a 10.2% recovery. The glycoprotein (39.1% carbohydrate content) showed an estimated molecular mass of 60 kDa. Optimum temperature and pH for its activity were 30–40 °C and 5.0, respectively. It showed a half-life (t50) of 60 min at 45 and 50 °C, and it was stable at pH 5.0 and 6.0 for 3 h. The tannase activity was insensitive to most salts used, but it reduced in the presence of Fe2(SO4)3 and FeCl3. On contrary, in presence of SDS, Triton-X100, and urea the enzyme activity increased. The Km value indicated high affinity for propyl gallate (3.61 mmol L−1) when compared with tannic acid (6.38 mmol L−1) and methyl gallate (6.28 mmol L−1), but the best Kcat (362.24 s−1) and Kcat/Km (56.78 s−1 mmol−1 L) were obtained for tannic acid. The purified tannase reduced 89 and 25% of tannin content of the leather tannery effluent generated by manual and mechanical processing, respectively, after 2-h treatment. The total phenolic content was also reduced. Additionally, the enzyme produced propyl gallate, indicating its ability to do the transesterification reaction. Thus, A. fumigatus CAS-21 tannase presents interesting properties, especially the ability to degrade tannery effluent, highlighting its potential in biotechnological applications.
Keywords: Aspergillus; Propyl gallate; Submerged fermentation; Tannery effluent; Tannic acid; Tannin acyl hydrolase